Method for making gradational diffusion photoelectric diode by using MOCVD epitaxial system - TANG QI; QIN LONG; WU RUIHUA (2010)
The invention relates to a method for making a gradational diffusion photoelectric diode by using an MOCVD epitaxial system. The method comprises the following steps performed on a semi-insulating indium phosphide substrate by using the MOCVD epitaxial system: performing the primary epitaxy of the photoelectric diode; forming an indium gallium arsenide ohmic contact layer; doping by using an MOCVD epitaxial system-based gradational diffusion method; making a pseudo-table by using a method combining reactive ion etching and chemical wet etching; making a second step by using a chemical wet etching method; making a SiO2 passivation layer and a photosensitive surface; evaporating an etching electrode; thinning the substrate and performing back sputtering and electrode alloying. Zinc phosphide is continuously generated during the diffusion and the method has the advantages of high doping, low ohmic contact resistance and high responsibility; moreover, abrupt junctions are formed during the diffusion, the dark cur